Friction Energy-Based Wear Simulation for Radial Shaft Sealing Ring - Flavien Foko Foko; Julia Heimes; Balázs Magyar; Bernd Sauer (Lubricants, 2020)
Radial shaft sealing rings (RSSR) are important machine elements used in rotating and oil lubricated systems. Their main task is to prevent oil from exiting the system and dirt particles from entering the system. When this function is not fulfilled, a leakage can occur and cause excessive damage after certain operating times, such as gear failure due to insufficient lubrication. This is the reason for the high level of current research interest in seals. The sealing function of RSSR occurs in the contact area between the sealing lip and the shaft. The contact takes place over a very small contact width of approximately 1 μm. These extremely small dimensions and the complex relationships between the functional influencing variables on the radial shaft sealing system make it difficult to simulate wear on the sealing ring. The energetic consideration of the wear process offers the possibility of quantifying influencing variables more easily by their energetic contribution, which can be determined experimentally. Based on experimentally measured total friction moments, and with the help of a semi-analytical (SA) solid contact model based on the half-space theory, this paper presents a modelling approach for the calculation of wear at the sealing ring. The model presented in this work differs from the existing models in two ways. The first particularity is the coupling of SA method with finite element method (FEM) for the resolution of the contact between the sealing lip and the shaft, allowing a fine discretization of the contact zone (by SA method) and the consideration of the structural behavior (by FE method). The SA method compared to the commonly used FEM presents a great saving in computation time. The second particularity is the use of the real data obtained during the wear tests. Most existing simulation models are based purely on contact pressure. This means that through the contact pressure obtained by simulation and a given sliding distance value, a friction energy will be estimated which will be used in a next step using a wear model such as Archad’s to calculate the wear rate. In this publication the value of friction energy was obtained directly on an experimental basis and a more appropriate wear law, such as Fleischer’s, taking into account the friction conditions, was used to estimate the wear rate.